Answer:
The answer is the demonstration, which is in the step-by-step explanation.
Step-by-step explanation:
Composite functions:
( f ᵒ g )(x) = f(g(x))
( g ᵒ f )(x) = g(f(x))
a)
f(x) = 2x
g(x) = x/2
[tex]f(g(x)) = f(\frac{x}{2}) = 2\frac{x}{2} = x[/tex]
[tex]g(f(x)) = g(2x) = \frac{2x}{2} = x[/tex]
Then
[tex]f(g(x)) = g(f(x)) = x[/tex]
b)
f(x) = 2x - 6
g(x) = (x + 6)/2
[tex]f(g(x)) = f(\frac{x+6}{2}) = 2\frac{x+6}{2} - 6 = x + 6 - 6 = x[/tex]
[tex]g(f(x)) = g(2x - 6) = \frac{2x - 6 + 6}{2} = \frac{2x}{2} = x[/tex]
Then
[tex]f(g(x)) = g(f(x)) = x[/tex]